Critical Thinking Processes on High-Order Thinking Skill Problems in the Problem-Based Learning Model - Ardiansyah; Radia Hafid; Cristian Polamolo; Nurul Maulida Alwi (Jurnal Pendidikan dan Pengajaran, 2026)
The low level of students’ critical thinking skills in dealing with contextual economic problems has become one of the challenges in Economics learning at the senior high school level. Students often experience difficulties in analyzing problems, evaluating information, and drawing logical conclusions when faced with questions that require Higher Order Thinking Skills (HOTS). This study aims to analyze students’ critical thinking processes in solving HOTS questions in Economics through the implementation of the Problem Based Learning (PBL) model. This research employed a mixed methods approach with a sequential explanatory design. The research subjects were eleventh-grade senior high school students who were purposively selected into two classes, namely an experimental group and a control group, each consisting of 30 students. Data collection methods included HOTS-based pretests and posttests, observations of the learning process, and interviews, with the main instrument being essay tests that measured critical thinking indicators. Quantitative data analysis was conducted through normality tests, homogeneity tests, independent t-tests, paired t-tests, and N-gain calculations, while qualitative data were analyzed descriptively to describe students’ critical thinking processes. The results showed a significant improvement in the critical thinking skills of the experimental group compared to the control group. In addition, students in the experimental group were more capable of going through the stages of critical thinking in problem-solving activities. This study concludes that the Problem Based Learning (PBL) model is effective in improving students’ critical thinking skills in answering HOTS questions in Economics learning. Therefore, its implementation is important to support learning oriented toward the development of higher-order thinking skills.